A community outbreak of group A beta haemolytic streptococci with transferable resistance to erythromycin. - Scott, R. J. (Cambridge University Press, 1989)
Erythromycin resistance amongst group A streptococci (GAS) in Great Britain is a relatively rare occurrence and outbreaks have been sporadically reported. Over an 8-month period in 1986 ten associated cases occurred in the town of Bridgewater in Somerset. Isolates were group A, type M4 and resistant to erythromycin (MIC 8 mg/l) but sensitive to lincomycin and clindamycin. Erythromycin resistance was transferable from all isolates to a group A recipient strain. No plasmid DNA could be detected in the original isolates or transconjugants.